Shigella: Antibiotic-Resistance Mechanisms And New Horizons For Treatment - Ranjbar, Reza (Infect Drug Resist, 2019)
Shigella spp. are a common cause of diarrheal disease and have remained an important pathogen responsible for increased rates of morbidity and mortality caused by dysentery each year around the globe. Antibiotic treatment of Shigella infections plays an essential role in reducing prevalence and death rates of the disease. However, treatment of these infections remains a challenge, due to the global rise in broad-spectrum resistance to many antibiotics. Drug resistance in Shigella spp. can result from many mechanisms, such as decrease in cellular permeability, extrusion of drugs by active efflux pumps, and overexpression of drug-modifying and -inactivating enzymes or target modification by mutation. Therefore, there is an increasing need for identification and evolution of alternative therapeutic strategies presenting innovative avenues against Shigella infections, as well as paying further attention to this infection. The current review focuses on various antibiotic-resistance mechanisms of Shigella spp. with a particular emphasis on epidemiology and new mechanisms of resistance and their acquisition, and also discusses the status of novel strategies for treatment of Shigella infection and vaccine candidates currently under evaluation in preclinical or clinical phases.